Accessibility analysis of the integrated transit system of Bogotá. Issue 4 (20th April 2016) - Bocarejo, Juan Pablo; Escobar, Daniel; Hernandez, Daniel Oviedo; Galarza, Diana
ABSTRACT: The new integrated transit system of Bogotá (ITSB) is a local initiative to improve general transportation conditions in the city. However, as an integral intervention to improve current transit services, it affects travel times and user costs, entailing changes in accessibility. We developed a methodology to calculate these changes for different areas in the city, considering travel expenditure for work trips and socioeconomic features of the population. The article evaluates accessibility implications for different fare schemes for the ITSB, modeling accessibility as a function of total travel expenditure and travel times. We focus on analyzing changes in cost and trip distribution for ITSB routes and their impacts on access to employment. Changes in travel attributes are obtained from a four-step transport model of Bogotá developed with VISUM modeling software. Meaningful changes in travel time and expenditure were found for all scenarios altering accessibility considerably. Under a flat fare scenario independent of travel distances, the number of transfers had a higher effect on accessibility in comparison to schemes where transfers are penalized through an incremental fare.